Calculation of temperature distribution in heavy oil reservoirs by electromagnetic heating - Gonzalez Alvarez, Herling; Pinzon Dıaz, Alberto Raul; Delgadillo Aya, Claudia Lorena; Muñoz Mazo, Eduin Orlando (CT&F - Ciencia, Tecnología y Futuro, 2023)
The introduction of heat into a reservoir has proven to be an effective way to reduce the viscosity of heavy oils by increasing the temperature in the formation. The use of electromagnetic energy has proven to be particularly attractive because of its advantages vis-à-vis conventional heat recovery techniques. While extensive research has been conducted on this radiofrequency recovery method over the years, numerical simulation with reservoir industry applications has been rarely used for electromagnetic heating with heavy oil reservoirs when connected to strong-bottom aquifers. We propose a numerical scheme to estimate temperature variations in the reservoir by electromagnetic absorption, based on the calculation of the electro- magnetic wavefield amplitude and radiation heat diffusion coupling. The electrical and thermal properties of the reservoir were calculated considering the fractions and saturation of its phases. The results obtained from this RF heating simulation show a radially distributed temperature profile within the reservoir. The power and frequency of the incident wave were considered for an antenna located in the center of the formation. This allows to determine the required energy in kWh, and its influence on the antenna power, as well as the thermal and electrical properties of the medium such as aquifers. Numerical modelling allows reaching a stable temperature inside the reservoir, in days or months, despite the strong presence of water-saturated zones. The simulation shows that the presence of aquifers at bottom and partially saturated media affects reservoir heating. To make the numerical experiment reproducible and verifiable, the workflow is provided in code form.